2010
DOI: 10.1007/s13225-010-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

Scleroramularia gen. nov. associated with sooty blotch and flyspeck of apple and pawpaw from the Northern Hemisphere

Abstract: Scleroramularia is proposed as a new hyphomycetous fungal genus associated with sooty blotch and flyspeck (SBFS) blemishes of apple and pawpaw fruit in the Northern Hemisphere. Morphologically the genus closely resembles Ramularia (Mycosphaerellaceae), based on its chains of hyaline conidia, with thickened, darkened, somewhat refractive conidiogenous loci. Scleroramularia is distinguished by forming black sclerotial bodies in culture, and having conidial chains that do not quickly disarticulate as observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 26 publications
(35 reference statements)
0
5
0
1
Order By: Relevance
“…Acremonium and Diatrypaceae have been widely reported to be isolated from desert halophytes and showed the ability to improve host resistance to biotic stress (Jalili et al, 2020 ; Ameen et al, 2021 ). However, Scleroramularia and Gaeumannomyces have been reported as pathogens of crops (Coombs et al, 2004 ; Li et al, 2011 ), which may be related to the transformation of endophytic fungal lifestyle. Studies have shown that the phase of endosymbiosis represents a balanced interaction between fungal virulence and host defense factors (Kuo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acremonium and Diatrypaceae have been widely reported to be isolated from desert halophytes and showed the ability to improve host resistance to biotic stress (Jalili et al, 2020 ; Ameen et al, 2021 ). However, Scleroramularia and Gaeumannomyces have been reported as pathogens of crops (Coombs et al, 2004 ; Li et al, 2011 ), which may be related to the transformation of endophytic fungal lifestyle. Studies have shown that the phase of endosymbiosis represents a balanced interaction between fungal virulence and host defense factors (Kuo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from single-conidium isolates that had grown on PDA plates at 25°C in darkness for 4 to 6 wk. DNA was extracted from the mycelium according to the protocol of Li et al [ 24 ]. Four genes were amplified: the internal transcribed spacer region (ITS), the partial β-tubulin gene (TUB2), the nuclear large subunit rDNA gene (LSU) and the DNA dependent RNA polymerase II largest subunit (RPB1).…”
Section: Methodsmentioning
confidence: 99%
“…Template DNA for polymerase chain reaction (PCR) was obtained by scraping mycelium from single-conidium isolates that had been grown on PDA plates for 4 to 6 weeks. DNA was extracted from the mycelium according to the protocol of Li et al [23] . The internal transcribed spacer region (ITS) of ribosomal DNA was amplified for all 63 isolates using primer pair ITS1-F/ITS4 [24] .…”
Section: Methodsmentioning
confidence: 99%